Anti-aging super-hydrophobic cold-applied crack sealant for asphalt pavement and preparation method thereof

CN123004359APending Publication Date: 2026-10-30DONGYING LUDONG LUQIAO CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611194085.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-07
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0003]现有常温型灌缝胶虽解决了施工加热问题,但普遍存在两大技术缺陷:一是长期暴露于紫外线和湿热环境中容易老化脆裂,失去密封效果;二是缺乏疏水特性,难以有效阻断水分沿裂缝的毛细渗透

Benefits of technology

1、本发明灌缝胶可在环境温度下直接挤出或刮涂施工,无需现场加热,25℃粘度为3200 mPa·s,操作简便,避免了能源消耗和有害气体排放。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses an asphalt pavement anti-aging super-hydrophobic normal-temperature gap filling glue and a preparation method thereof, and belongs to the technical field of road engineering materials. The gap filling glue is composed of the following raw materials in mass fractions: 100 parts of petroleum asphalt, 10-20 parts of SBS modifier, 8-15 parts of plasticizer, 15-30 parts of rubber powder, 0.5-2 parts of antioxidant, 0.5-2 parts of ultraviolet absorber, 1-3 parts of silane coupling agent, 3-8 parts of hydrophobic modified nano silicon dioxide and 5-15 parts of solvent. The hydrophobic modified nano silicon dioxide is subjected to fluorosilane surface treatment, the antioxidant is a hindered phenol type, and the ultraviolet absorber is a benzotriazole type or a hindered amine type. In the preparation, the hydrophobic modified nano silicon dioxide is prepared first, and then the asphalt is modified, composite modification is carried out, super-hydrophobic components are added and viscosity adjustment is performed in sequence. The gap filling glue can be directly constructed at normal temperature, the surface water contact angle after curing is greater than or equal to 150 degrees, the rolling angle is less than or equal to 10 degrees, has excellent super-hydrophobic waterproof effect, and the service life is significantly prolonged due to the synergistic anti-aging effect of the hindered phenol antioxidant and the ultraviolet absorber.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of crack sealant technology, and in particular to an anti-aging superhydrophobic room temperature crack sealant for asphalt pavement and its preparation method. Background Technology

[0002] my country's highway transportation development is progressing rapidly. Currently, highway infrastructure has transitioned from a construction phase to a phase emphasizing both construction and maintenance, with a focus on maintenance, making maintenance a challenging task. Asphalt pavements, during their service life, are susceptible to damage from traffic loads and ambient temperatures, leading to issues such as cracks, rutting, and potholes. Cracks are among the most common early-stage defects. Once cracks appear, rainwater seeps into the pavement structure, weakening the adhesion between asphalt and aggregates. Furthermore, the dynamic water pressure generated under traffic loads accelerates pavement fatigue damage, ultimately resulting in serious defects such as potholes and loosening. Therefore, timely sealing and grouting of cracks is a crucial preventative maintenance measure for asphalt pavements.

[0003] While existing room-temperature crack sealants have solved the heating problem during construction, they generally suffer from two major technical drawbacks: first, they are prone to aging and cracking when exposed to ultraviolet light and humid environments for extended periods, losing their sealing effect; second, they lack hydrophobic properties, making it difficult to effectively block the capillary penetration of water along cracks. Superhydrophobic materials, with their water contact angle ≥150° and roll-off angle ≤10°, have already seen mature applications in self-cleaning, anti-icing, and waterproofing fields, but reports of their introduction into asphalt pavement crack sealant systems are rare. The main technical obstacles are: poor compatibility between hydrophobic modified nanoparticles and the asphalt matrix, leading to agglomeration and phase separation; and the lack of a mature technical approach for effectively migrating superhydrophobic components to the surface and forming a stable micro / nano structure during the room-temperature curing process of the sealant.

[0004] To address the aforementioned issues, this invention systematically integrates superhydrophobicity and a dual anti-aging system into a room-temperature sealant. Superhydrophobicity is achieved by constructing a micro-nano rough surface structure using fluorosilane-modified nano-silica. The sealant synergistically resists thermo-oxidative and photo-oxidative aging through a combination of hindered phenolic antioxidants and ultraviolet absorbers. Simultaneously, silane coupling agents are used to improve the interfacial compatibility between inorganic nanoparticles and the organic asphalt matrix, giving the sealant convenient room-temperature application, long-lasting sealing, and active waterproofing functions. Summary of the Invention

[0005] The present invention aims to solve the above-mentioned problems. In its first aspect, the present invention provides an anti-aging superhydrophobic room-temperature crack sealant for asphalt pavements, composed of the following raw materials in parts by weight: 100 parts petroleum asphalt, 10-20 parts SBS modifier, 8-15 parts plasticizer, 15-30 parts rubber powder, 0.5-2 parts antioxidant, 0.5-2 parts ultraviolet absorber, 1-3 parts silane coupling agent, 3-8 parts hydrophobic modified nano silica, and 5-15 parts solvent; The hydrophobically modified nano-silica is obtained by surface hydrophobic modification of nano-silica with fluorosilane; the antioxidant is a hindered phenolic antioxidant; and the ultraviolet absorber is a benzotriazole or hindered amine ultraviolet absorber.

[0006] Furthermore, the petroleum asphalt is 90# or 110# road petroleum asphalt; the rubber powder is 80~120 mesh waste tire rubber powder; and the plasticizer is naphthenic oil or paraffin oil.

[0007] Furthermore, the fluorosilane is 1H,1H,2H,2H-perfluorodecyltriethoxysilane; the silane coupling agent is γ-aminopropyltriethoxysilane (KH550) or γ-glycidoxypropyltrimethoxysilane (KH560).

[0008] Furthermore, the petroleum asphalt is 110# road petroleum asphalt, the SBS modifier is 18 parts, the plasticizer is naphthenic oil and is 10 parts, the rubber powder is 100 mesh waste tire rubber powder and is 20 parts, and the hydrophobic modified nano silica is 3 parts.

[0009] Furthermore, the antioxidant is 1.0 part and the ultraviolet absorber is 1.0 part.

[0010] In a second aspect, the present invention provides a method for preparing an anti-aging superhydrophobic room-temperature crack sealant for asphalt pavement as described in the first aspect, comprising the following steps: (1) Preparation of hydrophobic modified nano silica: Nano silica was ultrasonically dispersed in anhydrous ethanol, fluorosilane modifier was added, and the mixture was stirred at 60~80℃ for 6~12 hours. After centrifugation, washing and drying, hydrophobic modified nano silica was obtained. (2) Asphalt modification: Petroleum asphalt is heated to 140~160℃, SBS modifier and plasticizer are added, and sheared for 30~60 minutes under shearing and stirring conditions, with the temperature controlled at 160~180℃, to obtain SBS modified asphalt; (3) Composite modification: Cool the SBS modified asphalt from step (2) to 120~140℃, add rubber powder, antioxidant, ultraviolet absorber and silane coupling agent, and stir for 30 minutes; (4) Addition of superhydrophobic components: Cool down to 100~120℃, add the hydrophobic modified nano silica prepared in step (1), and stir at low speed for 15~30 minutes; (5) Viscosity adjustment: Cool down to 80~100℃, add solvent, stir evenly and then cool to room temperature to obtain the finished product.

[0011] Furthermore, the rotation speed of the shearing and stirring in step (2) is 2000~4000 rpm; the rotation speed of the low-speed stirring in step (4) is 500~1000 rpm.

[0012] Furthermore, in step (1), the mass ratio of nano-silica to fluorosilane is 1:0.10~0.20, the reaction temperature is 65~75℃, and the reaction time is 7~9 hours.

[0013] Thirdly, the present invention provides a method for applying anti-aging superhydrophobic room temperature crack sealant to asphalt pavement as described in the first aspect. The sealant is applied directly to the surface of cracks in asphalt pavement by means of extrusion, scraping or spraying at an ambient temperature of 0~40℃, and the construction is completed after curing.

[0014] The present invention has the following beneficial effects: 1. The sealant of this invention can be directly extruded or scraped at ambient temperature without on-site heating. Its viscosity at 25°C is 3200 mPa·s. It is easy to operate and avoids energy consumption and harmful gas emissions.

[0015] 2. This invention achieves superhydrophobicity by incorporating 3 parts of fluorosilane-modified nano-silica, resulting in a water contact angle of 152° and a roll-off angle of 8° after the sealant has cured. Comparative studies show that without this component, the contact angle is only 95°, and the weight gain from water rinsing increases from 0.15% to 2.85% after 24 hours, demonstrating that F-SiO2 plays a decisive role in constructing superhydrophobic surfaces and blocking capillary water penetration.

[0016] 3. This invention has a dual anti-aging synergistic effect. The hindered phenolic antioxidant and the benzotriazole ultraviolet absorber are combined to inhibit thermo-oxidative aging and photo-oxidative aging respectively, and the two work synergistically. After 1000 hours of UV aging, the strength retention rate is 89%, and after thermo-oxidative aging, the elongation retention rate is 88%, which is far superior to the blank group (42%, 38%) and the single additive group, demonstrating a synergistic effect.

[0017] 4. The superhydrophobic structure of this invention indirectly enhances durability. After removing F-SiO2, even with the same anti-aging agent, the strength retention rate after UV aging decreases from 89% to 51%. The superhydrophobic surface actively repels moisture, blocking the water-oxygen-UV coupling aging path, so that the contact angle remains at 150° after aging, significantly improving long-term durability.

[0018] 5. The sealant of this invention has excellent comprehensive performance, with a softening point of 86.8℃, an ductility of 55.8 cm at 5℃, a bonding strength of 0.72MPa, and an elongation at break of 398%. It takes into account both high and low temperature performance and mechanical properties, effectively extending the service life of the sealant and reducing the cost of maintenance throughout the entire cycle. Detailed Implementation

[0019] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. The following embodiments are only for illustrating the present invention, and are not intended to limit the scope of the present invention in any way. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Unless otherwise specified, the experimental methods used in the present invention are conventional methods. Unless otherwise specified, the materials, reagents, etc. used in the present invention can be obtained commercially. In addition, other terms used in the present invention, unless otherwise specified, generally have the meanings commonly understood by those skilled in the art.

[0020] Example 1: Preparation of Superhydrophobic Modified Nano-Silica This embodiment provides a method for preparing hydrophobically modified nano-silica with fluorosilane surface, the specific steps of which are as follows: 1.1 Raw material preparation: Weigh 10.0 g of nano-silica (average particle size 20~50 nm, purity ≥99.5%, specific surface area 150~200 m² / g) and place it in a 500 mL three-necked flask. Measure 200 mL of anhydrous ethanol and 10 mL of deionized water, mix them thoroughly, and add them to the three-necked flask. The volume ratio of anhydrous ethanol to deionized water is 20:1.

[0021] 1.2 Ultrasonic dispersion A three-necked flask was placed in an ultrasonic cleaner and ultrasonically dispersed at room temperature for 30 min to ensure thorough dispersion of nano-silica in anhydrous ethanol / water mixed solvent, forming a homogeneous and stable suspension. The ultrasonic frequency was 40 kHz and the power was 200 W.

[0022] 1.3 pH Adjustment Under mechanical stirring (300-500 r / min), add 1 mol / L hydrochloric acid aqueous solution dropwise to the above suspension to adjust the pH of the system to 3-4. Stir continuously during the adjustment process to ensure a uniform pH throughout the system.

[0023] 1.4 Fluorosilane Addition and Reaction Weigh 1.5 g of 1H,1H,2H,2H-perfluorodecyltriethoxysilane (PFDTES, purity ≥97%) and add it dropwise to a three-necked flask at a rate of 1 drop per second using a constant pressure dropping funnel. The mass ratio of the nano-silica to the fluorosilane is 1:0.15. After the addition is complete, raise the system temperature to 70℃ and reflux the reaction under constant temperature magnetic stirring (400 r / min) for 8 h.

[0024] The control of reaction temperature and time is crucial to the modification effect. When the temperature is below 60℃, the reaction rate is too slow and the grafting rate is too low; when the temperature is above 80℃, fluorosilanes are easily volatilized and lost, and nanoparticle aggregation may occur. The preferred reaction temperature is 65~75℃ and the reaction time is 7~9 h.

[0025] During the reaction, the ethoxy group (-OCH2CH3) of the fluorosilane hydrolyzes under acidic conditions to generate silanol groups (Si-OH), which then undergo a dehydration condensation reaction with the active silanol groups (Si-OH) on the surface of nano-silica to form stable Si-O-Si covalent bonds, thereby grafting long perfluoroalkyl chains (-CF2-CF2-...-CF3) onto the surface of nano-silica. The perfluoroalkyl chains have extremely low surface energy (approximately 6~10 mN / m), transforming the modified nano-silica surface from hydrophilic to strongly hydrophobic.

[0026] 1.5 Separation and Washing After the reaction was complete, the suspension was allowed to cool naturally to room temperature. The mixture was then centrifuged at 8000 r / min for 10 min, and the lower precipitate was collected. The precipitate was washed three times with anhydrous ethanol and twice with deionized water to remove unreacted fluorosilane monomers and reaction byproducts.

[0027] 1.6 Drying The washed precipitate was placed in a vacuum drying oven and dried at 60°C for 12 hours until constant weight was obtained, yielding hydrophobically modified nano-silica (F-SiO2), a white powdery solid. It was sealed and stored away from light for later use. Light protection is crucial to prevent moisture absorption, which would increase the surface energy and affect the superhydrophobic effect.

[0028] 1.7 Performance Measurement Table 1

[0029] Example 2: Screening of Asphalt Modification Mix Proportions This embodiment uses a systematic single-factor screening experiment to determine the optimal mix ratio for asphalt modification by considering the base asphalt grade, SBS modifier dosage, and plasticizer type and dosage. All single-factor tests were conducted according to the following basic steps: petroleum asphalt was heated to 140-160°C, SBS modifier and plasticizer were added, and the mixture was sheared for 30-60 minutes under shear-stirring conditions, with the temperature controlled at 160-180°C, to obtain SBS-modified asphalt.

[0030] Experimental materials: Base asphalt: 90# and 110# road petroleum asphalt, which must meet the JTG F40 standard; SBS modifier: Linear SBS, must meet industrial grade requirements; Plasticizers: Naphthenic oil (N4010), paraffin oil (KP6030), must meet industrial grade requirements; Rubber powder: 80 mesh, 100 mesh, and 120 mesh waste tire rubber powder, which must meet industrial grade requirements and have a rubber hydrocarbon content of ≥48%.

[0031] Test metrics: Penetration (25℃, 100g, 5s) shall be in accordance with GB / T 4509; softening point (ring and ball method) shall be in accordance with GB / T 4507; ductility at 5℃ shall be in accordance with GB / T 4508; rotational viscosity at 180℃ shall be in accordance with GB / T 0624; segregation softening point difference shall be in accordance with GB / T 3681.

[0032] 2.1 Single-factor test for screening base asphalt grades Using a fixed mix ratio of 100 parts petroleum asphalt, 14 parts SBS modifier, and 10 parts naphthenic oil, comparative tests were conducted using 90# and 110# petroleum asphalt, and relevant indicators were measured. The details are shown in Table 2 below. Table 2

[0033] Analysis of experimental data shows that the ductility at 5℃ of 10# asphalt is 41.8% higher than that of 90# asphalt (46.5 cm vs 32.8 cm), indicating that its low-temperature crack resistance is significantly better than that of 90# asphalt. Although its softening point is slightly lower by 4.1℃, it can still reach above 80℃ after SBS modification, meeting the requirements for high-temperature use in road surfaces. For room-temperature crack sealant, low-temperature flexibility is the core performance indicator, and 110# road petroleum asphalt was selected as the base asphalt.

[0034] 2.2 Screening of SBS Modifier Dosage Using 100 parts of 110# petroleum asphalt and 10 parts of naphthenic oil as a fixed ratio, comparative tests were conducted with SBS modifier dosages of 10, 14, 18, and 22 parts, respectively, and relevant indicators were measured. The details are shown in Table 3 below. Table 3

[0035] Analysis of the experimental data shows that when the SBS content increases from 10 parts to 18 parts, the softening point increases by 12.3℃, and the ductility at 5℃ increases by 51.1%, demonstrating a significant modification effect. However, when the SBS content increases to 22 parts, the viscosity at 180℃ reaches 4.05 Pa·s, far exceeding the acceptable upper limit of 3.0 Pa·s for application, and the cost increases significantly, along with processing energy consumption. With an SBS content of 18 parts, all indicators show excellent performance, and the viscosity is 3.18 Pa·s, slightly higher than the target value, which can be adjusted to the viscosity for application at room temperature by adding solvent later. Therefore, this application selects an SBS content of 18 parts.

[0036] 2.3 Screening of Plasticizer Types and Dosage Using 100 parts of 110# petroleum asphalt and 18 parts of SBS as a fixed ratio, naphthenic oil and paraffin oil were selected as plasticizers, and comparative tests were conducted with 6, 10, and 14 parts respectively. The relevant indicators were measured, as shown in Table 4 below: Table 4

[0037] Analysis of experimental data shows that naphthenic oil exhibits significantly better ductility at 5°C than paraffin oil at all addition amounts, and also shows a significantly lower oil separation rate. This indicates that naphthenic oil has better compatibility with asphalt and SBS, and can more effectively insert itself between asphaltene molecules, improving low-temperature deformation capacity without significantly sacrificing high-temperature performance. Paraffin oil, at a dosage of 14 parts, has a softening point that has decreased to 79.8°C, below the preferred target of 80°C. Therefore, this invention determines naphthenic oil as the plasticizer type.

[0038] 2.4 Optimal Mix Proportion for Asphalt Modification Based on the single-factor screening tests in sections 2.1 to 2.3 above, the present invention determines the optimal mix ratio for asphalt modification as follows: 100 parts of 110# road petroleum asphalt, 18 parts of SBS modifier, and 10 parts of naphthenic oil plasticizer.

[0039] Samples were prepared using the above optimal ratio, and the comprehensive performance indicators are shown in Table 5 below: Table 5

[0040] In summary, the optimal asphalt modification formulation of this invention exhibits the following comprehensive performance analysis: its ductility at 5°C reaches 55.8 cm, ensuring that the sealant will not experience low-temperature brittleness when used in cold regions. Its softening point reaches 86.8°C, resisting the risk of softening and flowing under extreme summer road surface temperatures (up to 70°C). Its viscosity at 180°C is 2.95 Pa·s, facilitating further adjustment to a workable viscosity range at room temperature after adding solvents. The segregation difference is only 1.6°C, and the oil separation amount after 48 hours is only 0.25%, indicating good compatibility between SBS and asphalt, allowing for long-term storage without phase separation. This optimal asphalt modification formulation will serve as the base modified asphalt formulation for subsequent embodiments.

[0041] Example 3: Screening of a complete formula for a superhydrophobic, anti-aging, room-temperature grouting adhesive Using the optimal asphalt modification formulation obtained in Example 2 as the basic fixed formulation, a systematic multi-factor ratio optimization experiment was conducted by gradually adding rubber powder, antioxidant, ultraviolet absorber, silane coupling agent, superhydrophobic modified nano silica and solvent. The experiment focused on verifying the synergistic effect of the dual anti-aging system and the hydrophobic effect of superhydrophobic modified nano silica, and finally determined the complete formulation.

[0042] After each sample was prepared according to the complete process, the following key performance indicators were tested: Water contact angle, determined according to the static contact angle method; roll-off angle, determined according to the inclined table method; tensile bond strength (23℃), according to JT / T 740 method; elongation at break (23℃), according to JT / T 740 method; tensile strength retention rate after UV accelerated aging for 1000h, according to GB / T 16422.2 method; elongation at break retention rate after hot air aging for 80℃×168h, according to GB / T 3512 method; rotational viscosity at 180℃, according to GB / T 0624 method.

[0043] 3.1 Screening of Rubber Powder Fineness and Dosage Based on the basic formulation of Example 2 (100 parts of 110# asphalt + 18 parts of SBS + 10 parts of naphthenic oil), rubber powder was added. The fineness of the rubber powder was set at 80 mesh, 100 mesh, and 120 mesh, and the dosage was set at three levels: 15, 20, and 25 parts. Relevant indicators were measured, as shown in Table 6 below. Table 6

[0044] Analysis of the experimental data shows that 100-mesh rubber powder exhibits the best ductility and segregation stability at all dosage levels. At a dosage of 20 parts, the ductility at 5℃ reaches 61.5 cm, an 8.3% improvement compared to 15 parts, with an elastic recovery rate of 84%, demonstrating the best overall performance. At a dosage of 25 parts, the viscosity increases to 3.50 Pa·s, which will adversely affect the dispersion uniformity after the subsequent addition of superhydrophobic nanoparticles. Therefore, the rubber powder was determined to be 100-mesh waste tire rubber powder, with a dosage of 20 parts.

[0045] 3.2 Screening and Effect Verification of Superhydrophobic Modified Nano-Silica (F-SiO2) Dosage Based on the optimal result in 3.1, the formulation (100 parts of 110# asphalt + 18 parts of SBS + 10 parts of naphthenic oil + 20 parts of 100-mesh rubber powder) was supplemented with superhydrophobic modified nano-silica (F-SiO2) prepared in Example 1, with dosages of 0, 2, 3, 5, and 8 parts. Relevant indicators were measured, as shown in Table 7 below. Table 7

[0046] Analysis of the experimental data shows that when the F-SiO2 content is 0 parts, the water contact angle of the grouting adhesive surface is only 95°, which indicates that the surface is hydrophilic and water can spread and wet it, thus it does not have a waterproof barrier function.

[0047] When the F-SiO2 doping amount is 2 parts, the water contact angle increases to 132°, but still does not reach the threshold of superhydrophobicity ≥150°, indicating that the nanoparticles have insufficient surface coverage and have not yet formed a complete micro-nano rough structure, and the roll-off angle is still as high as 25°.

[0048] When the F-SiO2 doping concentration reaches 3 parts, the water contact angle abruptly increases to 152°, while the roll-off angle decreases to 8°, achieving superhydrophobicity. This is because when the nanoparticle coverage on the colloidal surface exceeds a critical value (approximately 60-70%), the solid-liquid contact mode changes from Wenzel wetting to Cassie-Baxter wetting, with the water droplet being supported by an air cushion, resulting in a sudden jump in the contact angle. At this doping concentration, the nanoparticles form a uniform and continuous micro-nano dual roughness structure on the surface, significantly reducing the actual contact area between the droplet and the rough surface.

[0049] When the dosage was further increased to 5 and 8 parts, the improvement in water contact angle slowed down (only increasing to 156° and 158°, respectively), but the viscosity at 180°C increased significantly (3.55 and 3.82 Pa·s), and the elongation at break decreased significantly (375% and 348%), which will have an adverse effect on the workability and material flexibility. In addition, excessive F-SiO2 is prone to agglomeration in the matrix, resulting in diminishing marginal benefits of superhydrophobic properties.

[0050] Therefore, the optimal doping amount of F-SiO2 is 3 parts, which can achieve the best balance between superhydrophobic effect (contact angle 152°, roll-off angle 8°) and mechanical properties (elongation at break 398%). At the same time, the performance improvement of more than 3 parts is extremely limited and the negative effects are aggravated.

[0051] 3.3 Screening and efficacy verification of anti-aging systems Based on the optimal results in 3.2 (100 parts of 110# asphalt + 18 parts of SBS + 10 parts of naphthenic oil + 20 parts of 100-mesh rubber powder + 3 parts of F-SiO2 + 2 parts of KH550 + 10 parts of 200# solvent oil), the comparative experimental groups shown in Table 8 were designed to verify the anti-aging effects of adding antioxidants and UV absorbers individually and in combination, and the relevant indicators were measured, as shown in Table 8 below. Table 8

[0052] Analysis of experimental data reveals that the antioxidant (hindered phenolic Irganox 1010) primarily inhibits the thermo-oxidative aging pathway by terminating the chain oxidation reaction by capturing peroxide free radicals (ROO•). The ultraviolet absorber (benzotriazole UV-326) reduces the damage to the chemical bonds of asphalt molecules by absorbing ultraviolet light in the 280-400 nm wavelength range and converting it into harmless heat energy. The two have different mechanisms of action and target different aging-inducing factors.

[0053] D0 (blank group): Without any anti-aging agent added, the contact angle dropped sharply from 152° to 108° after 1000 hours of UV aging. The superhydrophobic structure of the surface was completely destroyed, the strength retention rate was only 42%, and the elongation retention rate was only 38%, proving that unprotected sealant will quickly fail in outdoor environments.

[0054] D1 (with 1.5 parts antioxidant): The elongation retention rate after thermo-oxidative aging is increased to 78%, and the thermo-oxidative aging resistance is significant; however, due to the lack of ultraviolet absorber, the contact angle drops to 126° after UV aging, the strength retention rate is only 58%, and the surface micro-nano structure is destroyed under ultraviolet irradiation.

[0055] D2 (with 1.5 parts UV absorber): After UV aging, the contact angle remains at 135° and the strength retention rate is 62%, which is better than D1 in terms of anti-photoaging effect; however, due to the lack of antioxidant, the elongation retention rate after thermo-oxidative aging is only 51%, which is a weakness.

[0056] D3 (low-dose compound 0.5 + 0.5 parts): Both aging pathways were inhibited to some extent. After UV aging, the contact angle was 141°, the strength retention rate was 72%, and the elongation retention rate was 68%, all of which were better than any single anti-aging agent system. The synergistic effect of the compound has been initially demonstrated. However, the total dose is too low, and the protective effect is still insufficient.

[0057] D4 (optimal blend 1.0 + 1.0 parts): After 1000 hours of UV aging, the contact angle remained at 150°, the strength retention rate reached 89%, and the elongation retention rate after thermo-oxidative aging reached 88%. The dual anti-aging system forms synergistic protection along both UV and thermo-oxidative aging pathways: the antioxidant captures free radicals from within to slow down thermo-oxidative degradation, while the UV absorber absorbs UV radiation from the surface to prevent light energy from triggering a free radical chain reaction; the two complement each other. All indicators in this group met the optimal target (≥80%), making it the group with the best overall performance. The water contact angle decreased by only 2° before and after aging, proving that the superhydrophobic micro / nano structure was completely preserved under the protection of the dual anti-aging system.

[0058] D5 (high-dose compound 2.0+2.0 parts): its aging performance is slightly better than D4, but doubling the dosage does not bring significant performance gains (strength retention rate only increases from 89% to 90%), while the cost increases significantly, and excessive anti-aging agent may precipitate to the surface and affect the stability of the superhydrophobic structure.

[0059] Therefore, the optimal ratio was determined to be 1.0 part of antioxidant Irganox 1010 and 1.0 part of ultraviolet absorber UV-326. The antioxidant and ultraviolet absorber have a significant synergistic effect, and the combined effect of the two is far greater than the simple sum of the effects of using them alone, thus demonstrating a synergistic effect.

[0060] 3.4 Solvent Type and Dosage Screening Based on the optimal results in 3.3 (100 parts of 110# asphalt + 18 parts of SBS + 10 parts of naphthenic oil + 20 parts of 100-mesh rubber powder + 3 parts of F-SiO2 + 2 parts of KH550 + 1.0 part of antioxidant + 1.0 part of UV absorber), the effects of solvent type and dosage on the viscosity at room temperature were screened, and relevant indicators were measured, as shown in Table 9 below: Table 9

[0061] Analysis of experimental data shows that when the solvent is 200# solvent oil and the dosage is 10 parts, the viscosity at room temperature is 3200 mPa·s, which is suitable for extrusion or scraping application, and the overall cost is moderate.

[0062] 3.5 Optimal Formula Based on all the screening results above, the optimal formula is shown in Table 10 below: Table 10

[0063] The comprehensive performance indicators of the optimal formulation are shown in Table 11 below: Table 11

[0064] Comparative Example 1: Experimental Study on Removal of Superhydrophobic Components Based on the optimal formulation of 3.5, the superhydrophobic modified nano-silica (F-SiO2) component was removed, while the remaining components remained unchanged. The step of adding superhydrophobic modified nano-silica was skipped in the preparation process, with everything else remaining the same. The grouting adhesives prepared in Example 3 and Comparative Example 1 were cast into standard specimens using the same method. After curing for 7 days under the same conditions, various performance tests were conducted, and the results are shown in Table 12 below. Table 12

[0065] (1) Decisive influence on superhydrophobic properties In Comparative Example 1, without the addition of F-SiO2, the water contact angle of the sealant surface was only 95°, exhibiting typical hydrophilic characteristics (contact angle <90° is hydrophilic, 90~150° is hydrophobic, and ≥150° is superhydrophobic). Water droplets spread out in a flattened elliptical shape on the surface and could not roll off. Its surface energy was approximately 38 mN / m, which is within the typical surface energy range of asphalt-based materials.

[0066] In contrast, in Example 3, the addition of 3 parts F-SiO2 resulted in a sudden increase in the contact angle to 152°, achieving superhydrophobicity. This fundamental difference stems from the essential difference in surface microstructure: Example 3: During the colloidal curing process, F-SiO2 particles (20~50 nm) spontaneously migrate to the surface and are uniformly distributed on the micron-sized protrusions constructed from SBS / rubber powder, forming a double-rough structure of "micron-sized protrusions + nano-papillary protrusions" similar to a lotus leaf. Water droplets are supported by air cushions on this surface (Cassie-Baxter state), and the actual solid-liquid contact area accounts for only about 15~20% of the projected area.

[0067] Comparative Example 1: Contains no F-SiO2; the surface exhibits only micron-level undulations formed by SBS and rubber powder during curing, lacking nanoscale roughness. Water droplets directly contact and spread on the surface, exhibiting a Wenzel wetted state with no air cushion layer present.

[0068] (2) Fundamental impact on waterproof performance Because Comparative Example 1 lacks superhydrophobic properties, moisture can spread and wet the surface of the sealant and gradually penetrate to the interface between the sealant and the crack wall through capillary action. After 24 hours of dynamic water flushing, the weight gain of Comparative Example 1 was as high as 2.85% (moisture penetrated into the micropores inside the sealant), while the weight gain of Example 3 was only 0.15%, indicating that moisture could hardly penetrate.

[0069] In the 7-day static immersion test, there was no water penetration at the interface between the sealant in Example 3 and the crack wall, while the water penetration height at the interface in Comparative Example 1 reached 12.5 mm, and the water had risen along the interface, which could easily cause bond failure during freeze-thaw cycles.

[0070] (3) Indirect but crucial effects on resistance to aging durability The most noteworthy finding of this comparative example is that even though Comparative Example 1 and Example 3 contain the exact same hindered phenolic antioxidant and benzotriazole UV absorber (1.0 part each), their performance retention rate after aging is still much lower than that of Example 3. Specifically: After 1000 hours of UV aging, the strength retention rate of Comparative Example 1 was only 51% (compared to 89% in Example 3), a decrease of nearly three times that of Comparative Example 1.

[0071] After thermo-oxidative aging, the elongation retention rate of Comparative Example 1 was only 52% (compared to 88% in Example 3).

[0072] The underlying mechanism of this difference lies in the fact that moisture is a significant accelerating factor in asphalt aging. The hydrophilic surface of Comparative Example 1 allows moisture to spread and penetrate into the colloidal surface microcracks. Moisture carries dissolved oxygen and UV-induced free radicals deep into the material, accelerating the synergistic degradation process of thermo-oxidative and photo-oxidative aging (water-oxygen-UV coupled aging). In contrast, the superhydrophobic surface of Example 3 actively repels moisture, preventing it from remaining on the surface and penetrating, effectively blocking the chemical pathways through which moisture participates in and accelerates aging. Therefore, although F-SiO2 itself does not possess anti-aging chemical functions, it indirectly and significantly improves the actual protective efficiency of the dual anti-aging system through the mechanism of physically isolating moisture.

[0073] It is understood that those skilled in the art can make equivalent substitutions or modifications to the technical solutions and concepts of this invention, and all such substitutions or modifications should fall within the protection scope of the appended claims.

Claims

1. A superhydrophobic, room-temperature crack sealant for asphalt pavement anti-aging, characterized in that, It consists of the following parts by weight of raw materials: 100 parts petroleum asphalt, 10-20 parts SBS modifier, 8-15 parts plasticizer, 15-30 parts rubber powder, 0.5-2 parts antioxidant, 0.5-2 parts ultraviolet absorber, 1-3 parts silane coupling agent, 3-8 parts hydrophobic modified nano silica, and 5-15 parts solvent; The hydrophobically modified nano-silica is obtained by surface hydrophobic modification of nano-silica with fluorosilane; the antioxidant is a hindered phenolic antioxidant; and the ultraviolet absorber is a benzotriazole or hindered amine ultraviolet absorber.

2. The asphalt pavement anti-aging superhydrophobic room temperature crack sealant according to claim 1, characterized in that, The petroleum asphalt is 90# or 110# road petroleum asphalt; the rubber powder is 80~120 mesh waste tire rubber powder; the plasticizer is naphthenic oil or paraffin oil.

3. The asphalt pavement anti-aging superhydrophobic room temperature crack sealant according to claim 1, characterized in that, The fluorosilane is 1H,1H,2H,2H-perfluorodecyltriethoxysilane; the silane coupling agent is γ-aminopropyltriethoxysilane (KH550) or γ-glycidoxypropyltrimethoxysilane (KH560).

4. The asphalt pavement anti-aging superhydrophobic room temperature crack sealant according to claim 1, characterized in that, The petroleum asphalt is 110# road petroleum asphalt, the SBS modifier is 18 parts, the plasticizer is naphthenic oil and is 10 parts, the rubber powder is 100 mesh waste tire rubber powder and is 20 parts, and the hydrophobic modified nano silica is 3 parts.

5. The asphalt pavement anti-aging superhydrophobic room temperature crack sealant according to claim 1, characterized in that, The antioxidant is 1.0 part and the ultraviolet absorber is 1.0 part.

6. A method for preparing an anti-aging superhydrophobic room-temperature crack sealant for asphalt pavement as described in any one of claims 1 to 5, characterized in that, Includes the following steps: (1) Preparation of hydrophobic modified nano silica: Nano silica was ultrasonically dispersed in anhydrous ethanol, fluorosilane modifier was added, and the mixture was stirred at 60~80℃ for 6~12 hours. After centrifugation, washing and drying, hydrophobic modified nano silica was obtained. (2) Asphalt modification: Petroleum asphalt is heated to 140~160℃, SBS modifier and plasticizer are added, and sheared for 30~60 minutes under shearing and stirring conditions, with the temperature controlled at 160~180℃, to obtain SBS modified asphalt; (3) Composite modification: Cool the SBS modified asphalt from step (2) to 120~140℃, add rubber powder, antioxidant, ultraviolet absorber and silane coupling agent, and stir for 30 minutes; (4) Addition of superhydrophobic components: Cool down to 100~120℃, add the hydrophobic modified nano silica prepared in step (1), and stir at low speed for 15~30 minutes; (5) Viscosity adjustment: Cool down to 80~100℃, add solvent, stir evenly and then cool to room temperature to obtain the finished product.

7. The preparation method according to claim 6, characterized in that, The rotation speed of the shearing and stirring in step (2) is 2000~4000 rpm; the rotation speed of the low-speed stirring in step (4) is 500~1000 rpm.

8. The preparation method according to claim 6, characterized in that, The mass ratio of nano-silica to fluorosilane in step (1) is 1:0.10~0.20, the reaction temperature is 65~75℃, and the reaction time is 7~9 hours.

9. The method for applying anti-aging superhydrophobic room temperature crack sealant for asphalt pavement as described in any one of claims 1 to 5, characterized in that, At an ambient temperature of 0~40℃, the crack sealant is applied directly to the surface of asphalt pavement cracks by squeezing, scraping or spraying, and the construction is completed after curing.